Npas4 Expression in Two Experimental Models of the Barrel Cortex Plasticity. (16th February 2015) - Kaliszewska, Aleksandra; Kossut, Malgorzata
Abstract : Npas4 has recently been identified as an important factor in brain plasticity, particularly in mechanisms of inhibitory control. Little is known about Npas4 expression in terms of cortical plasticity. In the present study expressions of Npas4 and the archetypal immediate early gene (IEG) c-Fos were investigated in the barrel cortex of mice after sensory deprivation (sparing one row of whiskers for 7 days) or sensory conditioning (pairing stimulation of one row of whiskers with aversive stimulus). Laser microdissection of individual barrel rows allowed for analysis of IEGs expression precisely in deprived and nondeprived barrels (in deprivation study) or stimulated and nonstimulated barrels (in conditioning study). Cortex activation by sensory conditioning was found to upregulate the expression of both Npas4 and c-Fos. Reorganization of cortical circuits triggered by removal of selected rows of whiskers strongly affected c-Fos but not Npas4 expression. We hypothesize that increased inhibitory synaptogenesis observed previously after conditioning may be mediated by Npas4 expression.